(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
The PROCERTIF 225 white paper explores the emerging use of micro-credentials and digital proofs of competence in France, examining how organizations and learners perceive their value and how they are currently implemented. The study highlights both the growing interest in competency-based recognition and the conceptual confusion that still surrounds the field: a large majority of respondents report difficulty explaining the differences between micro-credentials, certifications, diplomas, and Open Badges. Despite this lack of clarity, organizations that issue proofs of competencies report overwhelmingly positive outcomes: 87% observe positive effects, while 13% report no significant effect and none report negative outcomes. For individuals, the benefits are primarily related to recognition and visibility of their skills. 38% of beneficiaries report that obtaining proof of competencies makes them feel valued, 33% say it allows them to be identified as competent within their organization, 18% highlight its usefulness for showcasing skills in their career plans, and 9% say it helps them become more aware of newly acquired competencies. The white paper also shows that the issuance of competency proofs is already practiced across several types of organizations. Training organizations represent 54% of current users, while adoption is also visible in the corporate sector, including 61% of large companies, 46% of medium-sized enterprises (ETI), and 18% of small and medium sized enterprises (SMEs). However, significant barriers still slow adoption. The most common obstacles include lack of knowledge about micro-credentials, technical complexity in implementation, organizational resistance to new forms of skill recognition, and doubts about their legitimacy outside traditional state-recognized certification systems. Overall, the report concludes that micro-credentials represent a promising but still maturing mechanism for recognizing competencies in professional contexts. Their wider adoption will depend on clearer frameworks, stronger interoperability between learning and credential infrastructures, and greater recognition of alternative ways of evidencing skills beyond traditional diplomas. Keywords: Micro-credentials · Skills recognition · Digital credentials · Workforce development